Influence of variation in indium concentration and temperature on the threshold current density in InxGa1-xAs/GaAs QD laser diodes - Zainab M. Alharbi; M.S. Al-Ghamdi (Heliyon)
The influence of variations in indium concentration and temperature on threshold current density (Jth) in InxGa1-xAs/GaAs (x = 0, 0.8 and 0.16) quantum dot (QD) laser diodes – synthesized via molecular beam epitaxy (MBE) with three distinct indium concentrations on GaAs (001) substrates – was meticulously examined. An X-ray diffraction (XRD) analysis revealed that increasing indium concentrations in InAs/InGaAs ‘dot in a well’ (DWELL) structures caused significant structural changes, including peak broadening and shifting, indicating increased lattice strain and potential defect formation. An investigation of light–current (L–I) characteristics revealed a super-linear increase in Jth up to the temperature of 323 K for all three lasers. Above 323 K, Jth exhibited an exponential increase, which is indicative of carrier leakage into the barriers from the quantum well. Additionally, Jth displayed a decreasing trend with increasing indium concentrations, suggesting enhanced QD symmetry and size from a higher indium content. A significant reduction in the characteristic temperature at which the threshold current occurred was observed as the indium concentration increased in the 288–363 K temperature range. Photoluminescence (PL) and electroluminescence (EL) measurements revealed a redshift of the lasing wavelength in correlation with higher indium concentrations. This redshift, attributable to variations in bandgap energy that decrease as indium content increases, highlights QD laser instability. These findings emphasize how versatile adjusting indium concentrations to tailor emission wavelengths can be and demonstrate potential applications in wavelength division multiplexing (WDM) systems and optical communications.